Minimally invasive lumbar pedicle screw fixation using cortical bone trajectory – Screw accuracy, complications, and learning curve in 100 screw placements. (March 2019) - Dayani, Fara; Chen, Yi-Ren; Johnson, Eli; Deb, Sayantan; Wu, Yunfen; Pham, Lan; Singh, Harminder
Highlights: Modified surgical technique and efficiency decreased late cohort complications. Smaller diameter screw resulted in fewer medial pedicle out-fractures and breaches. Cortical screws tended to stimulate at a lower electrical threshold. Abstract: Cortical bone trajectory (CBT) is a novel pedicle insertion technique with comparable or superior mechanical properties and reduced invasiveness compared to traditional methods. We describe the screw accuracy, complications, and learning curve associated with CBT use. A prospective cohort study was performed involving 22 patients who underwent lumbar fusion with CBT screw placement. A total of 100 cortical screws were placed. Post-operative CT scans were reviewed to assess the adequacy of screw placement and calculate the incidence of vertebral body and pedicle breaches from cortical screw placement. Technique-related complications were examined. The entire surgical cohort was divided into two groups: early experience (first 11 patients) and late experience (last 11 patients), to study the effect of learning curve on CBT screw placement. Medial pedicle breach was observed in 6/100 cases and lateral vertebral body breach was observed in 1/100 cases. The incidence of durotomy related to the technique was 4.5% (N = 1/22). Post-surgical wound infection was seen in 9.1% of patients (N = 2/22). 66.7% (N = 4/6) of medial pedicle breaches, 100% (N = 1/1) of lateral breaches, 100% (N = 1/1) of CBT technique-related CSF leaks, and 100% (N = 2/2) of wound infections occurred in the early experience phase of our study ( p = 0.0945 ). A shift in surgical technique and greater efficiency over time decreased the incidence of overall complications in the late cohort. The difference, however, did not reach statistical significance. A lateralized starting point for the cortical screw on the pars interarticularis and use of smaller diameter screws resulted in fewer medial pedicle out-fractures and breaches.